A Structured Literature Review of the Tourism Area Life Cycle Concept - Gore, Surabhi; Borde, Nilesh; Hegde Desai, Purva; George, Babu (Journal of Tourism, Sustainability and Well-being, 2022)
The tourism area life cycle is used to map the changes within the tourism destination on a temporal basis. The paper reviews the literature on the tourism area life cycle from 2003-2020. Articles appearing in journals having a cite score of 1.0 or higher were considered for the review process. The paper uses a structured review methodology and a widely accepted technique of content analysis to review the articles. The tourism area life cycle, as a concept, has traced its lifecycle. However, the use of the tourism area life cycle for tourism planning and strategy analysis is lacking. The authors recommend tourism area life cycle based research on macro-environmental and tourism-specific factors to identify strategies at the destination. Ex-post-facto research seeks to reveal the correlational relationship between the variables responsible for destination development. The paper also suggests tourism area life cycle research on accommodation units, restaurants, transport, infrastructure, market segments, and tourism attractions.